Edukasi Pemberian Imunisasi Pada Bayi Dan Balita Di Posyandu Nila B - Fitri Rahmadini, Annisa; Amelia, Dhea; Iklimah, Iik; Handayani, Prima (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Vaccination can increase the body's immunity and fight infectious diseases. The level of health of the Indonesian people is decreasing due to the high infant mortality rate, and one effort to overcome this is with a vaccination program for babies and young children. But this program still faces a problem: opposition from parents. Some say that parents' reluctance to vaccinate is caused by people's misunderstanding about vaccines, lack of education, lack of knowledge about vaccines, and the distance between Posyandu Nilla A and Posyandu Nila B, some argue that it is the same whether they want to carry out immunization or not, they will still experience fever, some say the reason is related to religion. This intervention aims to provide education to mothers who do not have access to basic health services. The method used is a lecture method using booklet media which provides direct information to mothers of babies and young children through open interaction. The results of the intervention showed that 81.0% of mothers had good knowledge and 19.0% of mothers had poor knowledge. The conclusion from this intervention is that most mothers know about vaccinations for their children, and it is hoped that good knowledge can help support good vaccinations for their children